Using Mask Reduces Respiratory Problems Among the Workers of Ship Breaking Industry (Journal of Dhaka National Medical College & Hospital, 2016)
The cross-sectional study showed that using facial mask reduces respiratory problems among the workers of the ship breaking industry. The study was conducted at Shitakund, Chittagong. Total 150 respondents were selected. Majority of the workers were